2005
DOI: 10.4049/jimmunol.174.9.5593
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Antiviral and Allogeneic Activity of a Human Public CTL Clonotype by a Single Altered Peptide Ligand: Implications for Allograft Rejection

Abstract: Alloreactive T lymphocytes are central mediators of graft-versus-host disease and allograft rejection. A public CTL clonotype with specificity for the alloantigens HLA-B*4402 and B*4405 is often expanded to large numbers in healthy HLA-B*0801+ individuals, driven by cross-reactive stimulation with the common, persistent herpesvirus EBV. Since such alloreactive memory CTL expansions have the potential to influence transplantation outcome, altered peptide ligands (APLs) of the target HLA-B*0801-binding EBV pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…In contrast to the canonical t 1/2 models, most T-cell activation studies suggesting that K D is a better predictor of ligand potency have k on larger than or close to the rebinding threshold (5,6). Our data suggest that these correlations with K D occur because …”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast to the canonical t 1/2 models, most T-cell activation studies suggesting that K D is a better predictor of ligand potency have k on larger than or close to the rebinding threshold (5,6). Our data suggest that these correlations with K D occur because …”
Section: Discussioncontrasting
confidence: 61%
“…Although ligand potency could be dependent on each of these binding characteristics, research over the past two decades has suggested that only the K D or t 1/2 matters. Mechanistically, these two mutually exclusive models have been interpreted to mean that T cells are either (i) sensitive to the number of TCRs simultaneously bound to pMHC (3)(4)(5)(6) or (ii) sensitive to ligands that produce a long enough interaction to phosphorylate the TCR complex fully (8-11, 13). In seeming contradiction to both theories, data presented here suggest that neither the K D nor t 1/2 determines the potency of T-cell ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis has confirmed that the anti-EBV response is sufficiently broad to accommodate the specific loss of the allocross-reactive subset while maintaining viral control (46). This suggests that approaches such as those developed by Burrows et al (49,50) describing the use an altered peptide ligand to an EBV epitope have the potential to antagonize the allospecific response without incapacitating EBV control.…”
Section: Heterologous Immunity: Good News For Protective Immunity Butmentioning
confidence: 65%
“…53), monkeys (38), rodents (39 -50, 54), and rainbow trout (51). The sharing of TCRs between individuals has also been observed in a variety of immune responses, including both acute (8,12,33,45,46,48) and persistent infections (10, 14, 15, 19 -21, 25-27, 29, 30, 32, 34 -38), autoimmune diseases (9, 11, 13, 16 -18, 22-24, 49, 50, 54), alloreactive states (28,31,42,43), and tumor rejection (41). Moreover, studies have suggested that public TCRs may play specific roles in many immune responses.…”
mentioning
confidence: 99%